LIABILITI BAGI PENIPUAN TORT DALAM FORENSIK - Ismail, Nurbazla; Mohamad, Abdul Basir (Jurnal Syariah, 2021)
Deceit is one branch of the offense under tort law. Deceit can be said to be a fraud act committed by someone who caused the other party to suffer loss or injury. The party suffering a loss or an injury can bring a claim in court on the basis of the tort law. Besides, the claimant must proof several important things before the court can decide the liability. This proof or evidence requires scientific verification by forensic experts. The testimony of the forensic expert can be used to convict deception and also can be used to dismiss the case in court. However, some forensic evidence is wrongly given in the trial. This has a significant effect on both the claimant and the defendant. As a result, the question arises as to what is the liability for tort of deceit in forensic according to tort and Islamic law. The purpose of this study is to define the meaning of deceit in tort and Islamic law as well as the liability for tort of deceit in forensic. This is a case study which gathered materials based on literature reviews, including cases published in Malaysian legal journals as well as cases addressed by fuqaha. The study was analyzed using thematic and descriptive methods. The study found that deceit is an offense according to tort and Islamic law. The liability for tort of deceit by a forensic expert must be determined on the grounds of which the deceit was knowingly committed while testifying to the evidence before the court. This study has implications to the judiciary; legal practitioners in Malaysia and to the forensic experts who were called to adduce evidence in court.